Household Composition and the Response of Child Labor Supply to Product Market Integration : Evidence from Vietnam - Edmonds, Eric V. (World Bank, Washington, DC, 2013)
Market integration raises the relative price of a community's export product. The author examines how the response of child labor supply to an increase in the relative price of a primary export product varies with a child's household composition. The specific context for his study is the liberalization of rice markets in Vietnam in the 1990s. Between 1993 and 1998, Vietnam lifted export restrictions on rice, allowing the domestic price to rise toward international levels, and eliminated internal restrictions on the flow of rice between regions of Vietnam. So, the relative price of rice increased overall in Vietnam, but the degree of price change varied across communities with the lifting of restrictions on internal flows. The author finds that the response of child labor supply to rice price increases is increasing the amount of time children work. Thus, household composition attributes that are associated with higher levels of child labor are also associated with larger declines in child labor with rice price increases. The results are consistent with girls particularly benefiting from product market integration because they work more than boys do. The results suggest that economic factors associated with economic reform may attenuate differences in the activities of siblings that are typically associated with cultural traditions and norms.